Diagnosing Internal Innovation Capability in Non-Food FMCG Product Development: Pengabdian - Stevani Tita Paramita; Isti Raafaldini Mirzanti (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Purpose − This study examines how internal innovation capabilities support new product development (NPD) and identifies the capability gaps that constrain execution in Indonesia's non-food fast-moving consumer goods (FMCG) industry. Design/methodology − The study uses a descriptive quantitative design and cross-company benchmarking. Survey data were collected from 49 practitioners involved in NPD across three anonymized non-food FMCG companies: the focal company, PT GCG, and two benchmark companies, GCA and GCB. Ten capability components were grouped into two layers - organizational foundation and managerial execution. The scores were normalized to a 0-1 scale and averaged to form the Internal Capability Index (ICI). Findings- PT GCG recorded an ICI of 0.506, placing it in the moderate capability band, below GCA (0.812; very good) and GCB (0.709; good). Its weakest absolute scores were concept development (0.412), external networks (0.426), and knowledge management (0.441). Relative to the average benchmark, the largest gaps appear in organizational structure, strategic alignment, and concept development. Concept development emerged in both diagnostic views, making it the clearest priority. The findings show that a single aggregate score is useful for positioning, but not sufficient for action. Combining absolute weaknesses with benchmark gaps produces a more practical basis for capability improvement.